Promoting an Integrated Science and English Pop-Up Book for Primary School Students - Rindu Handayani; Feni Kurnia (Linguists : Journal Of Linguistics and Language Teaching, 2022)
After doing an observation and interview with teachers, the researchers found that English and science were taught in a conventional method and were not thoroughly learnt. Hence, the teaching was not effectively conducted, and learning often ended up in boredom, which resulted in ineffective teaching and learning atmosphere. The objectives of this research were to create a combined English language and science pop-up book learning media for animal and human movement organs and to acknowledge its feasibility. The 4D development steps developed by S. Thiagarajan et al. were used in the research design, consisting of four stages: define, design, develop, and disseminate. The participants included in this research were the 5th-grade students of SD N 26 Belinyu, consisting of 35 students. Out of 35, 20 were female, and 15 were male. Two senior female teachers in the same school were also included in the interview. Data were collected by documentation, expert validation sheets, feasibility test sheets and user response questionnaires. Expert validation was conducted by two expert judgments, while language validation was justified by two language experts in Bahasa Indonesia and English. The results showed that the benefits students gain from using pop-up book media include seeing, opening, and shutting images on the pop-up book, which helps strengthen children's motor development.